Histological and Transmission Electron Microscopy Results after Embolization with HydroSoft/HydroFrame Coils in Experimental Swine Aneurysm. - Iseki, Seisuke; Mitome-Mishima, Yumiko; Ogino, Ikuko; Suga, Yasuo; Yatomi, Kenji; Nonaka, Senshu; Miyamoto, Nobukazu; Kondo, Akihide; Yamamoto, Munetaka; Arai, Hajime; Oishi, Hidenori (BioMed Research International, 2019)
Coiling and clipping are standard treatment strategies for cerebral aneurysms. Regardless of the strategy used, recanalization may affect the patient's prognosis. The aim of this study was to histologically and morphologically compare the tissue proliferation after coil embolization using bare platinum coils versus second-generation hydrogel coils (HydroSoft/HydroFrame; MicroVention, Inc., Aliso Viejo, CA, USA). Endothelial-like cell proliferation was seen in both groups at 2 weeks after surgery. Macroscopic findings showed a tighter layer at 4 weeks in the hydrogel coil group, and histological and immunohistochemical findings revealed endothelial cell proliferation. This layer became much thicker and tighter at 4 weeks after surgery. Aneurysms treated with second-generation hydrogel coils may be more stable and have a lower incidence of recanalization than those treated with bare platinum coils because of the tight endothelial layer proliferation.